2010
DOI: 10.1097/id.0b013e318200301a
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Pilot Study of Two Dental Implant Metals in a Pig Model

Abstract: This study revealed no significant short-term difference between the use of titanium and a chrome-cobalt alloy in implant effectiveness in the process of osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…49,50 Our study found that several methods were used to evaluate bone deposition on implant surfaces, and the most prevalent were histological and histomorphometric analyses. 34,36,40,51 These are effective techniques in analyzing bone-implant contact, which is considered the primary outcome in studies evaluating the osseointegration of dental implants. All the presented methods are well-grounded in the literature and have their peculiarities in terms of assessing peri-implant bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Our study found that several methods were used to evaluate bone deposition on implant surfaces, and the most prevalent were histological and histomorphometric analyses. 34,36,40,51 These are effective techniques in analyzing bone-implant contact, which is considered the primary outcome in studies evaluating the osseointegration of dental implants. All the presented methods are well-grounded in the literature and have their peculiarities in terms of assessing peri-implant bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 3 to 4 implants can be anchored per quadrant [ 284 ] with human or human-like implants 4 mm in diameter and 11 mm in length [ 286 ]. As for the tibia, the oral model may be useful for histological analyses such as cytotoxicity and viability of new compositions [ 287 , 288 , 289 , 290 ] but also for assessments on 1:1 scale models of mechanical properties [ 47 , 268 , 291 ], stress distribution [ 287 , 288 ], and the effects of different implant and abutment shapes [ 264 , 284 , 292 , 293 , 294 , 295 ]. Thanks to pigs having similar bone properties to those of humans, resistance to insertion [ 273 ] or removal torque can be measured during [ 296 ] or after healing [ 268 ].…”
Section: Appendix A1 Research In Non-human Primatesmentioning
confidence: 99%
“…It is possible to perform classical analysis such as measurement of bone area [ 273 ], marginal bone level [ 273 ], crestal bone loss [ 275 ], , resonance frequency [ 273 ], or implant stability quotient [ 297 ]. However, the main reason for selecting this site is almost always its suitability for bone-to-implant contact analysis [ 273 , 281 , 282 , 286 , 289 , 290 , 294 ]. This model is also used to assess the accuracy of new techniques, such as ultrasound imaging [ 298 ], comparison of intra-oral and cone beam computed tomography [ 299 , 300 ], magnetic resonance imaging [ 301 ], and resonance frequency analysis [ 302 ].…”
Section: Appendix A1 Research In Non-human Primatesmentioning
confidence: 99%